Oki stent application in different indications: Six cases - (:unkn) unknown (WILEY, 2018)
IntroductionWe have used Oki stents for a number of different indications. After discovering that there are limited reports in the literature on these stents, we were motivated to share our experiences in Oki stenting. ObjectivesWhile there is vast knowledge on double Y-stents, the Oki stent is a relatively recent development in pulmonology. Here, we demonstrate that stenting of the right secondary carina using an Oki stent should be considered for obstructions in this region. MethodsWe placed 13 mm x 10 mm x 9 mm Oki stents in six patients under general anesthesia via rigid bronchoscopy. ResultsThree cases were post-transplant patients with malacia, stenosis, and bronchopleural fistula. One case had an airway obstruction due to malignant disease, another case had a right aortic arc and aberrant left subclavian artery anomaly, and the final case had bronchopleural fistula. No serious complications were observed during stent placement. ConclusionsOki stents can safely be used for many clinical conditions. Patients benefit greatly from stenting; however, two of our cases died due to infection, and one case died due to malignancy.
Keywords: bronchomalacia; lung neoplasms; lung transplantation; silicones; stents; BIFURCATED SILICONE STENT; BRONCHOPLEURAL FISTULA; AIRWAY-OBSTRUCTION; DUMON STENT; BRONCHOSCOPY; STENOSIS